Research of the Laser Cladding and Wear-resistance of Worn Surface of Heavy Load Gear of Mining Machine - Zhao Ning; Tao Li; Guo Hui; Zhang Mengqi (Jixie chuandong)
Taking the worn out tooth surface of walking gear in JOY mining machine which imported from Germany as green re-manufacture study object,the anti-wear and anti-corrosion coating without crack nor pore is successfully produced by two techniques of fatigue layer removal and laser cladding in which parameters are optimized. The bonding state of laser clad coating and substrate interface is test,the wear-resistance of clad coating is systematically analyzed. The green re-manufacturing scheme in this study adopted high efficiency,rectangular spot laser technology combined with nickel based self-fluxing alloy produced comparatively flatter coating/substrate interface to conduct the study of re-manufacturing process. The slag and rust as well as fatigue spotting layer are completely removed from failure gear flank followed by laser incremental manufacturing and then the SEM analysis of the cross-section of laser cladding layer,wear resistance test is carried out. Finally a conclusion can be drawn,the re-manufacturing tooth surface produced by rectangular spot laser cladding has excellent wear resistance property,there is a high quality metallurgical bonding formed between laser cladding layer and the substrate gear,thus the work surface of gear has reached and surpassed the new product and properly matched the green re-manufacturing standard.